Contemporaneity and views from Expatria: past and current landscape practices. (2nd January 2023) - Galanopoulos-Papavasileiou, Ioannis; Hulbert, Shane
ABSTRACT: Views from Expatria: Photographing Place and the Self in Transience echoes the contradictory contexts of accelerated global migration and the recent pandemic border closures and controls. These conditions contribute creative parallels and new relationships to an escalating interest in concepts of place, home, expatriation and transience in contemporary society. As a creative-based research initiative using landscape photography as both a tool and methodology, the project reflects aesthetic trends, legacies and current debates about landscape photography and its contemporaneity. The paper critiques the literature and community of practitioners around concepts of non-place, home, transience and expatriation, and concepts central to the featured artist's photographic project Views from Expatria (2021). The paper also seeks to explore ways in which the practice is informed by contemporary photographic theories and practices.